Inoculant effects on fermentation characteristics, nutritive value, and mycotoxin concentrations of bermudagrass silage. Issue 1 (22nd August 2020) - Gouvêa, V.N.; Vendramini, J.M.B.; Sollenberger, L.E.; de Oliveira, F.C. Leite; Dubeux, J.C.B.; Moriel, P.; Cecato, U.; Soares Filho, C. V.; Sanchez, J.M.D.; Yarborough, J.K.; Kuhawara, F.
Abstract: Microbial inoculants have been used extensively to enhance silage fermentation characteristics; however, there is limited information about the effects of microbial inoculants on warm‐season perennial grass silage. The objective of this study was to examine the effects of commercial inoculants on mycotoxins, fermentation characteristics, and nutritive value of Jiggs bermudagrass [ Cynodon dactylon (L.) Pers.] silage. The experiment was conducted at Ona, FL, from June to October of 2014 and 2015. Treatments were seven commercial microbial inoculants (mixtures of homofermentative and heterofermentative bacteria: B500, Biotal Plus II, Early Sile Advance, Promote HQ, Promote VS‐3, F20, F600) and control (no inoculant) in a randomized complete block design with six replicates in each year. Mini‐silos were filled immediately after harvest and each treatment was sprayed using a hand sprayer before ensiling at rates recommended from the product manufacturer. There were no differences in pH, volatile fatty acids (VFA), ammonia nitrogen (NH3 ‐N), aerobic stability, and mold and yeast counts among treatments. In addition, silage dry matter (DM), crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), acid detergent insoluble crude protein (ADICP), total digestible nutrients (TDN), in vitro true digestibility (IVTD), and neutral detergent fiber digestibility (NDFD) did not differ among treatments. There was no presence of aflatoxin, zearalenone, and fumonisin in the silage. The inoculants evaluated herein did not affect nutritive value and fermentation characteristics of bermudagrass silage. The decision to add inoculants to bermudagrass silage must be made carefully due to inconsistent results and unlikely economic return.